Timeline of Rapid Eye Movement Sleep Behavior Disorder in Overt Alpha‐Synucleinopathies. Issue 2 (20th November 2020) - Stang, Cole D.; Mullan, Aidan F.; Hajeb, Mania; Camerucci, Emanuele; Turcano, Pierpaolo; Martin, Peter; Mielke, Michelle M.; Josephs, Keith A.; Bower, James H.; St Louis, Erik K.; Boeve, Bradley F.; Savica, Rodolfo
Abstract : Objective: The aim was to analyze the timeline, prevalence, and survival of rapid eye movement (REM) sleep behavior disorder (RBD) in patients who developed alpha‐synucleinopathies (Parkinson disease, dementia with Lewy bodies, and Parkinson disease dementia) compared with age‐ and sex‐matched controls in a population‐based incident‐cohort study. Methods: We used a population‐based, 1991 to 2010 incident‐cohort study of alpha‐synucleinopathies. A movement‐disorder specialist reviewed medical records to confirm diagnoses. RBD was diagnosed by reported dream‐enactment symptoms or polysomnography. Probable RBD and polysomnographically confirmed RBD were analyzed separately and combined. Results: Among the 444 incident cases of alpha‐synucleinopathy, 86 were clinically diagnosed with RBD (19.8%), including 30 (35%) by polysomnography and 56 (65%) as probable. The prevalence of idiopathic RBD at alpha‐synucleinopathy diagnosis was 3.4%, increasing to 23.8% after 15 years. Cumulative lifetime incidence was 53 times greater in alpha‐synucleinopathy patients than in controls (odds ratio [OR] = 53.1, 95% confidence interval [CI]: 13.0–217.2, p  < 0.0001), higher in dementia with Lewy bodies than in Parkinson disease (OR = 2.57, 95% CI: 1.50–4.40, p = 0.0004), and higher in men than in women with Parkinson disease, dementia with Lewy bodies, or Parkinson disease dementia (OR = 3.70, 95% CI: 2.07–6.62, p  < 0.0001), but did not increase mortality risk. Interpretation: Our cohort had RBD incidence of 3.4%. Overall RBD increased to 23.8% after 15 years, with an overall incidence of 2.5 cases per 100 person‐years. With 53 times greater lifetime incidence in alpha‐synucleinopathy patients than in controls, RBD was more likely to develop in dementia with Lewy bodies than in Parkinson disease or Parkinson disease dementia, and in men than in women, but did not increase mortality risk within our cohort. ANN NEUROL 2021;89:293–303